Integration of Islamic Law and Customary Law: The Kaboro Co'i Tradition in the Pre-Marital Practices of the Bima Community (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2025)
This study examines the Kaboro Co’i tradition practiced in the pre-marital ceremonies of the Bima (Dou Mbojo) community by analyzing its normative foundation and socio-cultural functions within the framework of maslahah (benefit) and Maqasid al-Shari‘ah (objectives of Islamic law) in Islamic Family Law. Employing a qualitative normative–empirical method, the research integrates textual analysis of Islamic legal sources with three months of fieldwork (June–August 2024) in Ntobo Village involving observations and semi-structured interviews with adat (customary) leaders, religious figures, community elders, and youth participants. The findings show that Kaboro Co’i, which encompasses ritual stages such as Panati, Nuntu Co’i, Mbolo Keluarga, Kalondo Fare, Wa’a Co’i, Zikir Labo Peta Kapanca, Lafa, and Walimah, embodies strong social values, including mutual assistance, deliberation, kinship maintenance, and togetherness. Traditional and community leaders view the tradition as culturally obligatory and religiously compatible, aligning with Maqasid al-Shari‘ah, particularly hifz al-din (protection of religion) and hifz al-nasl (protection of lineage). Normatively, it qualifies as ‘urf ṣaḥīḥ (valid custom) and substantively represents maslahah ḥājiyyah (complementary benefit) that supports family welfare, social harmony, and economic solidarity. Thus, Kaboro Co’i constitutes a form of living Islamic family law that harmonizes local wisdom with Islamic principles and remains socially relevant if it continues to promote communal welfare without creating socioeconomic burdens.